Cauliflower mosaic virus protein P6‐TAV plays a major role in alteration of aphid vector feeding behaviour but not performance on infected Arabidopsis. (15th May 2021) - Chesnais, Quentin; Verdier, Maxime; Burckbuchler, Myriam; Brault, Véronique; Pooggin, Mikhail; Drucker, Martin
Abstract: Emerging evidence suggests that viral infection modifies host plant traits that in turn alter behaviour and performance of vectors colonizing the plants in a way conducive for transmission of both nonpersistent and persistent viruses. Similar evidence for semipersistent viruses like cauliflower mosaic virus (CaMV) is scarce. Here we compared the effects of Arabidopsis infection with mild (CM) and severe (JI) CaMV isolates on the feeding behaviour (recorded by the electrical penetration graph technique) and fecundity of the aphid vector Myzus persicae . Compared to mock‐inoculated plants, feeding behaviour was altered similarly on CM‐ and JI‐infected plants, but only aphids on JI‐infected plants had reduced fecundity. To evaluate the role of the multifunctional CaMV protein P6‐TAV, aphid feeding behaviour and fecundity were tested on transgenic Arabidopsis plants expressing wild‐type (wt) and mutant versions of P6‐TAV. In contrast to viral infection, aphid fecundity was unchanged on all transgenic lines, suggesting that other viral factors compromise fecundity. Aphid feeding behaviour was modified on wt P6‐CM‐, but not on wt P6‐JI‐expressing plants. Analysis of plants expressing P6 mutants identified N‐terminal P6 domains contributing to modification of feeding behaviour. Taken together, we show that CaMV infection can modify both aphid fecundity and feeding behaviour and that P6 is only involved in the latter. Abstract : The viral protein P6, a major determinant of symptoms in infected plants, affects aphid behaviour in a way that could be favourable for transmission of cauliflower mosaic virus.